Tartrazine Removal from Aqueous Solution by HDTMA-Br-Modified Colombian Bentonite - Ronald A. Otavo-Loaiza; Nancy R. Sanabria-González; Gloria I. Giraldo-Gómez (The Scientific World Journal)
The effect of pH, ionic strength (NaCl added), agitation speed, adsorbent mass, and contact time on the removal of tartrazine from an aqueous solution, using an organobentonite, has been studied. A complete factorial design 32 with two replicates was used to evaluate the influence of the dye concentration (30, 40, and 50 mg/L) and amount of adsorbent (25, 35, and 45 mg) on decolorization of the solution. Experimental data were evaluated with Design Expert® software using a response surface methodology (RSM) in order to obtain the interaction between the processed variables and the response. pH values between 2 and 9, stirring speed above 200 rpm, and contact time of 60 min did not have a significant effect on decolorization. The optimum conditions for maximum removal of tartrazine from an aqueous solution of 30 mg/L were follows: pH = 6.0, NaCl concentration = 0.1 M, stirring speed = 230 rpm, temperature = 20°C, contact time = 60 min, and the organobentonite amount = 38.04 mg. The equilibrium isotherm at 20°C was analyzed by means of the Langmuir and Freundlich models, and the maximum adsorption capacity obtained was 40.79 ± 0.71 mg/g. This adsorption process was applied in a sample of industrial wastewater containing tartrazine and sunset yellow, having obtained a decolorization rate higher than 98% for both dyes. These results suggest that organobentonite is an effective adsorbent for the removal of anionic dyes from an aqueous solution.